Needs Analysis of English-Speaking Skills for Marine Tourism Professionals: Foundations for Developing Culture-Based ESP Materials - Widya Rizky Pratiwi; Effendi; Juhana; Celso P. Resueňo (Universitas Islam Negeri Palopo, 2026)
The rapid growth of marine tourism has increased the demand for English-speaking professionals capable of providing effective communication and high-quality services to international visitors. Although previous studies on English for Specific Purposes (ESP) have emphasized tourism English, they have primarily focused on general hospitality settings and language proficiency, with limited attention to workplace speaking competence in marine tourism and the integration of indigenous cultural values into instructional materials. This gap highlights the need for context-specific needs analysis to inform the development of authentic and culturally responsive ESP materials. Therefore, this study aimed to investigate the English-speaking needs of marine tourism professionals as a foundation for developing culture-based ESP speaking materials. Employing a descriptive mixed-methods design, the study was conducted among 24 marine tourism professionals in South Sulawesi, Indonesia, selected through purposive sampling from occupations involving direct interaction with international tourists. Data were collected using a researcher-developed needs analysis questionnaire comprising Likert-scale and open-ended items grounded in established ESP needs analysis frameworks. Quantitative data were analyzed descriptively using frequencies and percentages, while qualitative responses were examined through Braun and Clarke’s thematic analysis. The findings revealed that English speaking is perceived as an essential occupational competence for explaining destinations, answering tourists’ inquiries, handling complaints, introducing local culture, and facilitating intercultural communication. Participants also identified pronunciation, listening comprehension, complaint handling, and selecting contextually appropriate expressions as major communication challenges. Furthermore, they strongly preferred authentic workplace learning activities, practice-oriented speaking tasks, multimedia support, intercultural communication training, and the integration of Bugis hospitality values - Sipakatau, Sipakalebbi, Sipakainge', and Taro Ada Taro Gau - into ESP materials. This study contributes to the ESP literature by proposing a culture-based framework that integrates workplace communication, intercultural competence, and indigenous hospitality values to support the development of contextually relevant English-speaking materials for marine tourism professionals.